The importance of brand value in the view of the company’s assets - Kíra Martin; Szilágyi Nándor (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2023)
Abstract. Because of the economic and social changes in the past few decades, intangible assets, including the brand, play an increasingly decisive role in the economy, in the strategy formulation and in the business decisions of companies. Despite all of these, claiming the lack of a reliable measurement model, the current treatment of brand value in accounting, and thus its presentation in the financial statement is still unresolved, even though thanks to the transformation of the economy and market demands, many methods of brand valuation have emerged in theory and in practice as well. By using practical examples, the aim of this paper is to examine the importance of brands in the operation of companies, the weight of its value compared to the companies’ assets, and the legitimacy of the obstacle formulated by the standard setters, who are stating the lack of a reliable measurement model. The method used in this research is the case study research method that belongs to the paradigms of qualitative field research. By using the example of two well-known brands, it was verified that the brand plays an important role in the business decisions of the owner companies. The examined data also highlighted that the weight of the brand value is particularly significant in the reflection of the companies’ assets on the balance sheet, which proves that the stakeholders of the companies should receive information about it. Furthermore, it was concluded that the standard deviation of the results of the models currently used by the brand evaluation companies is too high in terms of the potential recognition on the balance sheet, so it is recommended to present the brand value in another way. The examination of the brand value of other companies using the case study method should be the subject of further research, which can provide a basis for finding the most effective way for stakeholders to get information about brand value, thereby eliminating criticisms of the financial statements’ usefulness in this regard.

Az elmúlt évtizedek gazdasági és társadalmi változásainak következtében a szakirodalom szerint az immateriális eszközök, így köztük a jelen kutatás tárgyát képező márka is egyre meghatározóbb szerepet tölt be a gazdaságban, a vállalatok stratégiájában és üzleti döntéseiben. Mindezek ellenére a megbízható mérési modell hiányára történő hivatkozással a márkaérték jelenlegi számviteli kezelése, így a beszámolóban történő bemutatása megoldatlan még, pedig a gazdaság átalakulásának és a piaci igényeknek köszönhetően a márkaértékelésnek az elméletben és a gyakorlatban is számos módszere alakult ki. Jelen tanulmány célja, hogy gyakorlati példák segítségével megvizsgálja a márka jelentőségét a vállalat gazdálkodásában, értékének súlyát a társaság vagyonához képest, valamint a standardalkotók által megfogalmazott akadálynak, a megbízható mérési modell hiányának jogosságát. A kutatásban használt módszer a kvalitatív terepkutatás paradigmai közé tartozó esettanulmány elemzés módszere. Ennek segítségével két ismert márka példáján nyert igazolást, hogy a márka fontos szerepet tölt be a tulajdonos vállalatok üzleti döntéseiben. A vizsgált adatok rávilágítottak arra, hogy a márkaérték súlya kifejezetten jelentős a vállalat mérlegében szereplő vagyonának tükrében, ami indokolja, hogy a vállalatok érdekeltjei tájékoztatást kapjanak róla. Megállapítást nyert továbbá, hogy a jelenleg a márkaértékelő cégek által használt modellek eredményeinek szórása a mérlegben való megjeleníthetőség szempontjából túlságos magas, így a márkaérték egyéb módon történő bemutatása javasolható. További kutatás tárgyát kell, hogy képezze, más vállalkozások márkaértékének esettanulmány módszerrel történő vizsgálata, ami alapot biztosíthat annak megtalálására, hogy mi lenne a leghatékonyabb módja annak, hogy a vállalatok érdekeltjei a márkaértékről információhoz juthassanak, kiküszöbölve ezzel a beszámoló hasznosságát e tekintetben érő kritikákat.

Резюме. В результаті економічних і соціальних змін, що відбулися за останні кілька десятиліть, нематеріальні активи, включаючи бренд, відіграють все більш вирішальну роль в економіці, у формуванні стратегії та в бізнес-рішеннях компаній. Незважаючи на це, необхідно вказати на відсутність в існуючих підходах надійної моделі вимірювання вартості бренду в бухгалтерському обліку, а отже, її представлення у фінансовій звітності досі не врегульоване, хоча завдяки трансформації економіки та вимогам ринку багато методів оцінки бренду виникли як в теорії, так і на практиці. Використовуючи практичні приклади, мета цієї роботи полягає в тому, щоб вивчити важливість брендів у діяльності компаній, долю їх вартості порівняно з активами компаній, а також правомірність перешкод, сформульованих розробниками стандартів, які стверджують про відсутність надійної моделі вимірювання. Метод, який використовується в цьому дослідженні, є методом кейс-стаді, який належить до парадигм якісних польових досліджень. На прикладі двох відомих брендів було перевірено, що бренд відіграє важливу роль у бізнес-рішеннях компаній-власників. Досліджені дані також підкреслили, що вага вартості бренду є особливо важливою для відображення активів компаній у балансі, що доводить, що зацікавлені сторони компаній повинні отримувати інформацію про це. Крім того, було зроблено висновок, що стандартне відхилення результатів моделей, які в даний час використовуються компаніями з оцінки брендів, є занадто високим з точки зору потенційного визнання в балансі, тому рекомендовано представляти вартість бренду в інший спосіб. Вивчення вартості бренду інших компаній за допомогою методу прикладів має стати предметом подальших досліджень, які можуть стати основою для пошуку найбільш ефективного для зацікавлених сторін способу отримати інформацію про вартість бренду, тим самим усуваючи критику фінансової звітності. корисність у цьому відношенні.
Важливість цінності бренду з позиції активів компанії
A márkaérték fontossága a vállalat eszközeinek szempontjából
https://aab-economics.kmf.uz.ua/aabe/issue/view/4
Keywords: brand; brand value; brand valuation methods; accounting; financial statement